2018
DOI: 10.1016/j.jweia.2018.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Towards LES as a design tool: Wind loads assessment on a high-rise building

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…They found that the turbulent wind inflow results in a larger mean and a fluctuating value of the drag coefficient. Extensive numerical studies have also been performed, generally achieving satisfactory agreement with experimental results (Tominaga et al 2008;Huang, Li & Wu 2010;Tominaga 2015;Yan & Li 2015;Ricci et al 2018;Thordal et al 2019). Investigations into the flow around high-rise buildings have so far focused predominantly on aerodynamic forces.…”
Section: Introductionmentioning
confidence: 82%
“…They found that the turbulent wind inflow results in a larger mean and a fluctuating value of the drag coefficient. Extensive numerical studies have also been performed, generally achieving satisfactory agreement with experimental results (Tominaga et al 2008;Huang, Li & Wu 2010;Tominaga 2015;Yan & Li 2015;Ricci et al 2018;Thordal et al 2019). Investigations into the flow around high-rise buildings have so far focused predominantly on aerodynamic forces.…”
Section: Introductionmentioning
confidence: 82%
“…10%). The procedure is similar to the one proposed by Bruno et al (2010) and adopted by Ricci et al (2018): the time history is divided into N D sub-windows of length T; then the average (or the standard deviation) φ n is computed over a time t n ¼ [0, nT], where n ¼ 1, 2 … N D . The residuals percentage is computed as: 1 for the points on the lateral sides, in agreement with experimental observations.…”
Section: Declaration Of Competing Interestmentioning
confidence: 99%
“…Many studies of tall buildings use smaller domains than those recommended above, but there is little consistency between the domain sizes used in such studies [e.g. (Braun and Awruch, 2009;Huang et al, 2007Huang et al, , 2011Ricci et al, 2018;Zhang et al, 2015)].…”
Section: Introductionmentioning
confidence: 99%